A Framework to Assess Where and How Children Connect to Nature - Giusti, Matteo; Svane, Ulrika; Raymond, Christopher M.; Beery, Thomas H. (Frontiers in Psychology, 2018)
The design of the green infrastructure in urban areas largely ignores how people’s relation to nature, or human-nature connection (HNC), can be nurtured. One practical reason for this is the lack of a framework to guide the assessment of where people, and more importantly children, experience significant nature situations and establish important nature routines. This paper develops such a framework. We employed a mixed-method approach to understand what qualities of nature situations connect children to nature (RQ1), what constitutes children’s HNC (RQ2), and how significant nature situations and children’s HNC relate to each other over time (RQ3). We first interviewed professionals in the field of connecting children to nature (N=26), performed inductive thematic analysis of these interviews, and then further examined the inductive findings by surveying further specialists (N=275). We identified sixteen qualities of significant nature situations (e.g., ‘awe’, ‘engagement of senses’, ‘involvement of mentors’) and ten abilities that constitute children’s HNC (e.g., ‘feeling comfortable in natural spaces’, feeling attached to natural spaces’, ‘taking care of nature’). We elaborated three principles to answer our research questions: 1) significant nature situations are various and with differing consequences for children’s HNC; 2) children’s HNC is a complex embodied ability; 3) children’s HNC progresses over time through diverse nature routines. Together, these findings form the Assessment framework for Children’s Human Nature Situations (ACHUNAS). ACHUNAS is a comprehensive framework that outlines what to quantify or qualify when assessing ‘child-nature connecting’ environments. It guides the assessment of where and how children connect to nature, stimulating both the design of nature-connecting human habitats as well as pedagogical approaches to HNC.